Using Alternative Cogeneration Plants in Iraqi Petroleum Industry (Journal of Engineering, 2014)
The present paper describes and analyses three proposed cogeneration plants include back pressure steam-turbine system, gas turbine system, diesel-engine system, and the present Dura refinery plant. Selected actual operating data are employed for analysis. The same amount of electrical and thermal product outputs is considered for all systems to facilitate comparisons. The theoretical analysis was done according to 1st and 2nd law of thermodynamic. The results demonstrate that exergy analysis is a useful tool in performance analysis of cogeneration systems and permits meaningful comparisons of different cogeneration systems based on their merits, also the result showed that the back pressure steam-turbine is more efficient than other proposals. Moreover, the results of the present work indicate that these alternative plants can produce more electric power than that required in the refinery. At present time, the industrial cogeneration plants are recommended in Iraq, especially in petroleum industry sectors, in order to contribute with ministry of electricity to solve the present crisis of electric power generation. Such excess in the power can sold to the main electric network. The economic analysis are proved the feasibility of the proposed cogeneration plants with payback period of four year and six months ,three year and eight months, and ten years for steam cogeneration plant, gas turbine cogeneration plant and diesel engine cogeneration plant respectively.